If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -3x = 2 + 4x Add '-2' to each side of the equation. 2 + -2 + -3x = 2 + -2 + 4x Combine like terms: 2 + -2 = 0 0 + -3x = 2 + -2 + 4x -3x = 2 + -2 + 4x Combine like terms: 2 + -2 = 0 -3x = 0 + 4x -3x = 4x Solving -3x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3x + -4x = 4x + -4x Combine like terms: -3x + -4x = -7x -7x = 4x + -4x Combine like terms: 4x + -4x = 0 -7x = 0 Divide each side by '-7'. x = 0 Simplifying x = 0
| ((2*t)/15)-(((3*t)-5)/20)=((t/5)-3) | | 14t-33=14t-8 | | 6(x-4)=-4 | | 56=71 | | 4e^5= | | 4e^5=x | | -2x+y=3y-6x | | 20x+5y=285 | | 3(y-1)=c | | 8x^2(4x^3+2x^2+3x+1)= | | -7(3x-4)=-49 | | 6(2x-1)=4x+18 | | (X-2)(x+6)=180 | | -3(1+5)+4=-104 | | 3-x/42 | | 5/7-3Y=-2 | | 6-5[4-(7y-2)]= | | -(2+x)=-3(x-2) | | -6(n+-2)+4(3+-6x)=-36 | | y=(x+9)m | | 4X^3/X^5=64 | | -6(n+-2)+4(3+-6x)=36 | | 2ln(x+2)=ln(x-1) | | 5f+7f+f= | | Y/85=6/10 | | .25x+.10y=2.85 | | 200x-.67=100x+81 | | 7n+16-5n=34 | | 5/2h15 | | r-1.2=11.5 | | 5x-8=7x+4 | | 9x/2-4=34 |